Cryobiopsy versus open lung biopsy in the diagnosis of interstitial lung disease (COLDICE): protocol of a multicentre study. Issue 1 (21st June 2019) - Troy, Lauren K; Grainge, Christopher; Corte, Tamera; Williamson, Jonathan P; Vallely, Michael P; Cooper, Wendy; Mahar, Annabelle M; Lai, Simon; Mulyadi, Ellie; Torzillo, Paul J; Salamonsen, Matthew; Don, Garrick; et al.
Abstract : Introduction: Transbronchial lung cryobiopsy (TBLC) is a novel, minimally invasive technique for obtaining lung tissue for histopathological assessment in interstitial lung disease (ILD). Despite its increasing popularity, the diagnostic accuracy of TBLC is not yet known. The COLDICE Study (Cryobiopsy versus Open Lung biopsy in the Diagnosis of Interstitial lung disease allianCE) aims to evaluate the agreement between TBLC and surgical lung biopsy sampled concurrently from the same patients, for both histopathological and multidisciplinary discussion (MDD) diagnoses. Methods and analysis: This comparative, multicentre, prospective trial is enrolling patients with ILD requiring surgical lung biopsy to aid with their diagnosis. Participants are consented for both video-assisted thoracoscopic surgical (VATS) biopsy and TBLC within the same anaesthetic episode. Specimens will be blindly assessed by three expert pathologists both individually and by consensus. Each tissue sample will then be considered in conjunction with clinical and radiological data, within a centralised MDD. Each patient will be presented twice in random order, once with TBLC data and once with VATS data. Meeting participants will be blinded to the method of tissue sampling. The accuracy of TBLC will be assessed by agreement with VATS at (1) histopathological analysis and (2) MDD diagnosis. Data will be collected on interobserver agreement between pathologists, interobserver agreement between MDD participants, and detailed clinical and procedural characteristics. Ethics and dissemination: The study is being conducted in accordance with the International Conference on Harmonisation Guideline for Good Clinical Practice and Australian legislation for the ethical conduct of research. Trial registration number: ACTRN12615000718549 .